Disentangling Host-Microbiota Regulation of Lipid Secretion by Enterocytes: Insights from Commensals Lactobacillus paracasei and Escherichia coli - Asmaa Tazi; João Ricardo Araujo; Céline Mulet; Ellen T. Arena; Giulia Nigro; Thierry Pédron; Philippe J. Sansonetti (mBio, 2018)
ABSTRACT The gut microbiota contributes to nutrients absorption and metabolism by enterocytes, but the molecular mechanisms involved remain poorly understood, and most conclusions are inferred from studies comparing germfree and conventional animals colonized with diverse bacterial species. We selected two model commensal microorganisms, Escherichia coli and Lactobacillus paracasei, to assess the role of the small-intestinal microbiota in modulating lipid absorption and metabolism by the epithelium. Using an integrated approach encompassing cellular and murine models and combining metabolic parameters measurement, lipid droplet imaging, and gene expression analysis, we demonstrated that under homeostatic conditions, L. paracasei promotes fat storage in enterocytes, whereas E. coli enhances lipid catabolism and reduces chylomicron circulating levels. The Akt/mammalian target of sirolimus (mTOR) pathway is inhibited by both bacterial species in vitro, indicating that several regulatory pathways are involved in the distinct intracellular lipid outcomes associated with each bacterial species. Moreover, soluble bacterial factors partially reproduce the effects observed with live microorganisms. However, reduction of chylomicron circulating levels in E. coli-colonized animals is lost under high-fat-diet conditions, whereas it is potentiated by L. paracasei colonization accompanied by resistance to hypercholesterolemia and excess body weight gain. IMPORTANCE The specific contribution of each bacterial species within a complex microbiota to the regulation of host lipid metabolism remains largely unknown. Using two model commensal microorganisms, L. paracasei and E. coli, we demonstrated that both bacterial species impacted host lipid metabolism in a diet-dependent manner and, notably, that L. paracasei-colonized mice but not E. coli-colonized mice resisted high-fat-diet-induced body weight gain. In addition, we set up cellular models of fatty acid absorption and secretion by enterocytes cocultured with bacteria and showed that, in vitro, both L. paracasei and E. coli inhibited lipid secretion, through increased intracellular fat storage and enhanced lipid catabolism, respectively.